Preservation of the lung function after thoracic irradiation - Vujasković, Željko (Radiology and oncology (Ljubljana), 1997)
TGF-beta is considered as a predictor of pneumonitis in patients receiving radiotherapy. Plasma TGF-beta levels were investigated in 27 consecutive patients with NSCLC stage III, who were treated with 60 Gy (2 Gy/day) radiotherapy with or without carboplatin. TGF-beta was measured with a biossayusing mink lung epithelial cells transfected with a plasminogen activator inhibitor-1 promoter-luciferase construct (normal values (Sd) 9.0 ng/ml (1.9)). Mean (SD) pretreatment TGF-beta value was 55.8 ng/ml (33). Only 3 patients had normal values. TGF-beta was not related to age, performance, score, or weight loss. No relationship between pretreatment TGF-beta levels and pneumonitis was observed. There was no influence of carboplatin or radiation field size on the incidence of pneumonitis nor on TGF-beta levels during treatment. All 9 patients who developed pneumonitis (CTC criteria) after treatment had, during radiotherapy, a high persistent TGF-beta levels relative to pretreatment levels. Patients with the same or lower TGF-beta values relative to pretreatment values did not developed symptomatic lung injury. In conclusion, elevated TGF-beta levels during radiotherapy may identify patients at high risk of developing pneumonitis after treatment. Furthermore, it can help in selection of those patients who might be candidates for dose escalation.
Keywords: Blood; Carboplatin; Luciferase; Lung neoplasms; Plasminogen activator inhibitor 1; Radiation pneumonitis; Radiotherapy; Respiratory function tests; Transforming growth factor beta